(untitled) (Research, Society and Development, 2022)
Pulpotomy is a conservative techinique that offers maintenance of the integrity of the thooth and its supporting tissues. Advances in the field of cellular and molecular biology have contributed to the advento f a series of new materials, more biocompatible, suitable for pulpotomy of primary teeth. The use of lasers has excelente impacto n pulpo therapy for these theeth, in such a way that it can replace pharmacotherapeutic techniques. The objective was to compares the effectiveness of lasers in pulpotomu of primary theeth, describing procedures and its influence on tissue repair, in addition to discussing its applicability in conjunction with materials of the Pulp tooth complex. A bibliographic survey was carried out in the Scielo, Lilacs, Bvs and Pubmed databases using the descriptors: “Dental pulp”, “Pulpotomy” and “Lasertherapy”. Of the eight articles considered by this integrative literature review, it was found that the most used lasers for the treatment of pulpotomy in human primary teeth are the Diode and Low Intensity Laser, being considered an excellent treatment alternative, as it presents satisfactory results for irradiated tissues. It was concluded that the Low Intensity Laser will be the choice for performing pulpotomy on primary teeth, as it contributes to the increase of metabolism, cell proliferation and maturation, amount of granulation tissue and reduction of inflammatory mediators, leading to the process healing.